Зміни глікемії під впливом цукрознижувальних засобів у щурів зі стрептозотоциновим діабетом на тлі висококалорійної дієти - Кіхтяк, О. П. (Clinical Endocrinology and Endocrine Surgery, 2011)
Effects of sensitizers (Metformin, Pioglitazone) and stimulator of insulin secretion (Glimepiride) in Fat-Fed Streptozotocin rats were studied. It was discovered that Metformin in dose of 500 mg/kg and Pioglitazone in dose of 30 mg/kg in comparison with Glimepiride in dose of 1 mg/kg per day affect carbohydrate metabolism in Fat-Fed Streptozotocin male Wistar rats. Metformin decreases fasting glucose level, and Pioglitazone more than Metformin is able to descent HbA1c in compare with the control group. Fat-Fed Streptozotocin model which supposes insulin resistance proves high affectivity of sensitizers.